(untitled) (Veterinary Science, 2017)
When attempting to recover mycobacterium through lab or environmental samples it´s necessary to apply a decontamination method that reduces the accompanying microbiota. It is possible to apply drastic decontamination methods due to the fact that mycobacterium presents a complex wall structure. There are several proposed methods, considering that the ideal method is the one that reduces accompanying microbiota without affecting the number of existing mycobacterium. The objective of this study was to determine decimal reduction of a mycobacterium strain suspension applying the decontamination methods proposed for soil samples, recreational water, tap water and fecal material. A mixed inoculum of mesophilic bacterium was determined (B M) commonly isolated from the environment and another one with a Mycobacterium porcinum strain recovered from tap water. Both inoculums were diluted until a suspension equivalent to a 1 tube of the Mc Farland scale was reached. The real number of bacterium was quantified using the dilution method with base 10. At the same time, three experiments were made to demonstrate decimal reduction when applying different decontaminations methods when trying to recover mycobacterium from soil (Iivanainen, 1995); wetlands (Leite et al., 1989); tap water (Engel et al., 1980); and fecal material (Stabel et al., 1997). Results obtained in this study demonstrated that the Leite et al. (1989) and the Stabel et al. (1997) methods reduced the total number of contaminating bacterium while the number of Mycobacterium porcinum were reduced by 3 and 4 log. Independently applying the methods of Iivanainen (1995) y Engel et al. (1980) reductions of 4 log were obtained in BM contaminants while in the Mycobacterium porcinum strain the reduction varied between 2,5 log and 1 log respectively. It is important to consider the mycobacterium reduction by each different method to correct mycobacterium count numbers in the environmental samples and also so that certain environments are not included as possible habitats of mycobacterium when they are not recovered by conventional methods due to the fact that they may be under the determined reduction value